Beauty for All Time -- In Plastics... - Dow Chemical Company (1946)
Color print advertisement for Styron, the trade name for Styrenic plastics historically manufactured and sold by the Dow Chemical Company for a variety of consumer applications. The advertisement features an illustration of a woman reclining in bed next to a clock with a plastic exterior. The accompanying text promotes the use of Styron and other Dow plastics in a variety of consumer goods.
Keywords: Advertising; Chemical industry; Corporations; Dow Chemical Company; Plastics; Plastics industry and trade; Women in advertising